Solvent‐Switching Gelation and Orange–Red Emission of Ultrasmall Copper Nanoclusters. Issue 2 (2nd December 2015) - Liu, Jinhua; Zhang, Qiang Matthew; Feng, Yong; Zhou, Zhengyuan; Shih, Kaimin
Abstract: By tuning the Cu⋅⋅⋅Cu and hydrogen‐bonding interactions, the small cluster Cu3 L can be selectively synthesized to develop a stable and highly fluorescent material, as confirmed by matrix‐assisted laser desorption ionization–time of flight mass spectroscopy. Further characterizations, including absorbance spectroscopy, XPS, and XRD demonstrate the formation of tiny Cu nanoclusters (NCs). In water, the as‐prepared Cu NCs can exhibit high orange fluorescence via solution evaporation to eliminate hydrogen‐bonding, and in dimethylformamide, a strong orange fluorescent gel is obtained by solvent induction to enhance the Cu⋅⋅⋅Cu and hydrogen‐bonding interactions. More importantly, the Cu NCs in their substantial form exhibit nonlinear optical properties upon two‐photon excitation. These results will shed light on Cu and related cluster applications in two‐photon biological imaging, optical power limiting, and solar energy conversion. Abstract : Cu nanoclusters can exhibit high orange fluorescence in dimethylformamide and the solid state by appropriately tuning the Cu⋅⋅⋅Cu and hydrogen‐bonding interactions.